Estimating Discharge in Seti Watershed of Gandaki Basin using Water Evaluation and Planning (OODBODHAN, 2025)
Accurate estimation of river discharge is essential for assessing water availability and supporting sustainable water resource development. While hydropower is considered a renewable energy source, its impacts on other water demands are often overlooked. Comprehensive water accounting is crucial to balance hydropower generation with competing needs, ensuring equitable and efficient water use. In a small country like Nepal, water resource management is often underprioritized due to the high costs, need for advanced tools, and reliance on specialized expertise. This study aims to estimate the discharge in the Seti Watershed of the Gandaki Basin using the Water Evaluation and Planning (WEAP) model, chosen for its integrated approach to simulating water availability, demand, and allocation. The hydrological model is developed with the goal of evaluating the software at the catchment level using criteria for assessing model efficiency. The modeling was conducted using the Runoff-Rainfall method, along with the soil moisture simulation method integrated within WEAP. The study area was divided into sub basins, allowing for a more detailed understanding of the runoff pattern. The study recorded a mean maximum monthly flow of 248 m3/s in August and a mean minimum monthly flow of 18 m3/s in March at the outlet point. Similarly, the highest mean monthly rainfall was observed in July at 1104.51 mm, while the lowest was recorded in December at 11.41 mm. The statistical performance of model for calibration was NSE = 0.82, R² = 0.82, PBIAS = -0.046%, and RSR = 0.42, while for the validation period, NSE = 0.84, R² = 0.93, PBIAS = 8.7, and RSR = 0.39. The results demonstrate the reliable efficiency of the software in performing hydrological modeling at the sub-basin level on a monthly basis. Additionally, the model can be used to estimate the discharge at each catchment outlet point and assess its efficiency.